1996
DOI: 10.1177/108201329600200104
|View full text |Cite
|
Sign up to set email alerts
|

Parámetros de color del jugo de granadilla (Passiflora edulis Sims): influencia de la época de cosecha de la fruta/ Color parameters of passion fruit juice (Passiflora edulis Sims): influence of harvest season

Abstract: This study covers the evolution of color parameters (L*, a*, b*) of passion fruit juice from 2 different seasons (winter and summer) and its relation with carotenoid content and also the sensory evaluation of juices. Three different harvests were made during the two seasons, every 15-20 days. Soluble solids/acidity ratio was used as a maturity index. Winter maturity index was 3.5 and summer index was 6.6: The carotenoids content for winter fruit was higher than that for summer fruit (2.6 and 1.7 mg β-carotene/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
4

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
1
0
4
Order By: Relevance
“…O valor de vitamina A foi de 78 equivalente de retinol/100 g da polpa da fruta, sem a separação de isômeros. Sepúlveda et al (1996) observaram que existem diferenças na cor do suco de P. edulis (variedade não especificada) em diferentes épocas de colheita. Observouse que o conteúdo de carotenoides na colheita de inverno é mais alto do que no verão, gerando, portanto, sucos com cor mais intensa.…”
Section: Carotenóidesunclassified
See 1 more Smart Citation
“…O valor de vitamina A foi de 78 equivalente de retinol/100 g da polpa da fruta, sem a separação de isômeros. Sepúlveda et al (1996) observaram que existem diferenças na cor do suco de P. edulis (variedade não especificada) em diferentes épocas de colheita. Observouse que o conteúdo de carotenoides na colheita de inverno é mais alto do que no verão, gerando, portanto, sucos com cor mais intensa.…”
Section: Carotenóidesunclassified
“…A vitamina C é talvez a mais investigada por ser um dos principais indicadores do valor nutritivo do suco. A variedade roxa, com 29,80 mg de ácido ascórbico/100 mL de suco em média, apresenta maior teor de vitamina C que a variedade amarela, que possui 20,0 mg de ácido ascórbico/100 mL de suco (Sepúlveda et al, 1996). Vinci et al (1995) utilizando CLAE, encontraram valores superiores para o maracujá amarelo fresco, 64,78 mg/100g, o que permite considerar o maracujá como uma fonte adicional de vitamina C na dieta.…”
Section: Vitaminasunclassified
“…Rind of 'Urussanga' genotype had the highest carotenoid content of all genotypes meanwhile 'Urussanga' juice had the lowest carotenoid content (along with Rubi and Catarina Roxo) (Table 2). Sepúlveda et al (1996) observed 1.57 to 3.22 mg equivalent β-carotene 100 g -1 in passion fruit (Passiflora edulis) and that the harvest season influences carotenoid content, with fruit grown during winter months yielding greater carotenoid content than those grown during summer months. Therefore, the cultivation of passion fruit in the southern colder regions has the potential to yield juices with more intense colors and higher contents of carotenoids.…”
Section: Resultsmentioning
confidence: 99%
“…Por otro lado, las CCMs con los demás sustratos (cocona, tomate, tuna) sus voltajes no muestran variaciones bruscas se mantiene con valores cercanos a 0.5 y 0.3 voltios desde el primer al último día de monitoreo. Sepúlveda et al menciona que la granadilla tiene un rendimiento de jugo solo entre el 22 y 53 % sobre la fruta entera, lo que podría explicar el por qué la CCM con este tipo de sustrato genera menor cantidad de voltaje, debido a que a menor cantidad de sustrato orgánico (combustible) menor seria la generación de voltaje [26]. Mientras que la CCM con sustrato de cocona que mostro menor perdida de voltaje durante el monitorio puede ser debido a los altos contenidos de salicilato de metilo, hidrocarburos de cadena larga, ácidos grasos y sus ésteres metílicos y etílicos [27]; los cuales fueron reportados como los compuestos que generar voltaje en CCM [28].…”
Section: Caracterización De Las Celdas De Combustible Microbianaunclassified